Comparison of Virginia Henderson's Theory to Abraham Maslow's Theory of Basic Human Concepts - Muhammad langlang Tahta Raharja; Rista Rista; Siti Nurul Kholif; Yuni Rohyani; Budi Prasetyo; Aris Prio Agus Santoso (Journal of Complementary in Health, 2022)
Basic human needs are a series of elements needed by humans to survive in order to remain in optimal conditions, there are various theories regarding basic human needs including the theory of Virginia Henderson and Abraham Maslow. This study aims to describe the comparison between Virginia Henderson's theory in more detail in discussing basic human concepts, compared to Abraham Maslow's theory. Nurses in carrying out nursing care must be in accordance with the principles of philosophy and nursing ethics in providing action to patients or clients. This research method uses an approach. Literature Study by identifying, reviewing, evaluating and interpreting all available research, the data obtained were analyzed quantitatively to describe the correlation between Virginia Henderson's theory and Abraham Maslow's theory. The results show that the comparison of Virginia Henderson's theory describes the definition of nursing by identifying 14 needs that underlie nursing care, while Abraham Maslow's theory describes the definition of nursing with 5 needs that underlie nursing care.